Development of Mathematics Teaching Materials Based on Realistic Mathematics Education Using Tri-N on Linear Equation System Material - Rina Sri Lestari; Akhmad Nayazik; Lenny Kurniati (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
Teaching materials are learning tools that contain materials, learning methods, and ways to evaluate students which are arranged systematically to achieve learning objectives. The teaching materials used during mathematics learning are textbooks that make it difficult for students to understand the material and educators have not developed teaching materials based on a realistic mathematics education using the Tri N teaching. This research aims to determine the validity and responses of students to the development of mathematics teaching materials based on realistic mathematics education using Tri N teaching on the material of linear equation system class X SMK. This type of research is Research and Development (R&D) which aims to produce and test product quality. This research refers to the 4D development model, namely Define, Design, Develop, and Disseminate. However, this research only reached the development stage. Data was collected by using documentation techniques, validation sheets, and student response questionnaires. The test subjects were students of class X TKJ 1 SMK Kesuma Margoyoso. The data analysis technique used is descriptive analysis. This research produces a product of mathematics teaching materials with an average percentage of 85.6% which is included in the very valid category. Student responses to teaching materials are in the very good category with an average percentage of 82.22%. This shows that teaching materials are suitable for use in learning at school. Keywords: teaching materials, realistic mathematics education, tri-n.